Swadaya Masyarakat dalam Pembangunan (Studi Tentang Pembangunan Jalan Usaha Tani di Desa Kalimendong Kabupaten Wonosobo) - Khaira Rusmantika; Turtiantoro .; Priyatno Harsasto (Journal of Politic and Government Studies, 2017)
Effort to improve the application of economic development model is to modernize in every aspect of community life that underlies every policy of development practice. The development-oriented model of economic growth, leads to the fragility of social society system. One of the component to support the development model is how to utilize the existing social capital in society. Most Indonesian people live in the rural areas with livelihood as farmer. The agricultural sector is a sector that has a large contribution in the national economy, the provision of road infrastructure is very supportive of the acceleration of economic growth. But in the provision of infrastructure facilities can never be separated from community involvement in every stage of activity itself. This research was conducted by using research method of mix method sequential exploratory sequence from qualitative descriptive approach as the dominant approach of quantitative approach as supporting approach. Data collection used in this research is interview, observation, documentation and questionnaire. The informant consisted of the head of development affairs of Kalimendong village, the head of Sido Makmur farmers, and the community, the questionnaire was given to the respondents of the Kalimendong village community. The results showed that the utilization of social capital in Kalimendong village done by Sido Makmur farmers which belong to social capital bridging that bringing of Kalimendong village community doing farming road construction with self-reliance. At each stage of development, the community is very enthusiastic to follow every activity although not supported by stimulant funds from the government. Activities are still carried out using self-reliance community to realize the activities. Farming road construction will be more optimal if the administration is in detail, and do not disappoint the community's trust.Keywords : Farming Road Construction, Self-reliance community